2003
DOI: 10.1074/jbc.m306922200
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profiling Identifies Genes That Continue to Respond to Insulin in Adipocytes Made Insulin-resistant by Treatment with Tumor Necrosis Factor-α

Abstract: We have employed microarray technology using RNA from normal 3T3-L1 adipocytes and from 3T3-L1 adipocytes made insulin-resistant by treatment with tumor necrosis factor-␣ to identify a new class of insulin-responsive genes. These genes continued to respond normally to insulin even though the adipocytes themselves were metabolically insulin-resistant, i.e. they displayed a significantly decreased rate of insulin-stimulated glucose uptake. Approximately 12,000 genes/expressed sequence tags (ESTs) were screened. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 53 publications
4
48
0
2
Order By: Relevance
“…ABCA1 is expressed in pancreatic ␤-cells and is regulated by a transcriptional regulatory network including several proteins and drugs involved in lipid and glucose metabolism (6,7). Moreover, insulin downregulates ABCA1 expression in vitro, while glucose upregulates ABCA1 expression in leukocytes in vivo (8,9). Very recently, mice with specific inactivation of ABCA1 in ␤-cells showed accumulation of cellular cholesterol, marked insulin secretion reduction in vivo, and progressive glucose tolerance impairment, establishing a pivotal role for ABCA1 in pancreatic ␤-cell function (10).…”
Section: T He Identification Of Atp-binding Cassette Transporter A1 (mentioning
confidence: 99%
“…ABCA1 is expressed in pancreatic ␤-cells and is regulated by a transcriptional regulatory network including several proteins and drugs involved in lipid and glucose metabolism (6,7). Moreover, insulin downregulates ABCA1 expression in vitro, while glucose upregulates ABCA1 expression in leukocytes in vivo (8,9). Very recently, mice with specific inactivation of ABCA1 in ␤-cells showed accumulation of cellular cholesterol, marked insulin secretion reduction in vivo, and progressive glucose tolerance impairment, establishing a pivotal role for ABCA1 in pancreatic ␤-cell function (10).…”
Section: T He Identification Of Atp-binding Cassette Transporter A1 (mentioning
confidence: 99%
“…Collectively, these observations raise the possibility that in the situation of metabolic insulin resistance accompanied by hyperinsulinemia, the expression of certain insulin-responding genes may dramatically increase in insulin target tissues. Expression profiling studies in adipocytes have identified a number of genes that continue to respond normally or are hyperresponsive to insulin even though the adipocytes themselves were metabolically insulin resistant; i.e., they displayed a significantly decreased rate of insulin-mediated glucose uptake (42). Identification of genes that continue to respond to insulin in an insulinresistant state such as obesity, in concert with studies of the properties of these genes and the signaling pathways that regulate them, may provide novel insights into the molecular mechanisms that control abnormal gene expression in obesity and provide novel opportunities for rational drug development.…”
Section: Diabetes Vol 55 September 2006mentioning
confidence: 99%
“…Insulin induces the production and secretion of substantial amounts of MCP-1 in insulin-resistant adipocytes and insulin-resistant obese mice [10]. MCP-1 is similar to other genes such as PAI-1 and SREBP-1c in that it continues to respond to exogenous insulin in insulin-resistant states [10,21]. Moreover, MCP-1 inhibits (by approximately 30%) insulin-stimulated glucose uptake into mouse adipocytes [10].…”
Section: Introductionmentioning
confidence: 99%